2014
DOI: 10.1152/ajpheart.00852.2013
|View full text |Cite
|
Sign up to set email alerts
|

PDE2-mediated cAMP hydrolysis accelerates cardiac fibroblast to myofibroblast conversion and is antagonized by exogenous activation of cGMP signaling pathways

Abstract: Recent studies suggest that the signal molecules cAMP and cGMP have antifibrotic effects by negatively regulating pathways associated with fibroblast to myofibroblast (MyoCF) conversion. The phosphodiesterase 2 (PDE2) has the unique property to be stimulated by cGMP, which leads to a remarkable increase in cAMP hydrolysis and thus mediates a negative cross-talk between both pathways. PDE2 has been recently investigated in cardiomyocytes; here we specifically addressed its role in fibroblast conversion and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…Furthermore, scanning and quantifying cGMP dependent PDE isoenzymes was performed on 12 days serum induced myofibroblasts and reveal 5 different transcript expression. Expression of these specific PDEs seems to have a central role in modulating cGMP (Qvigstad et al 2009, Vettel et al 2014, thus modulating the ANP/NPRA system. Lu et al (2013) quantified PDEs in TGF-β induced cardiac myofibroblasts obtained from Sprague-Dawley rats, and their studies have showed that cAMP can prevent the CFs to myofibroblasts transformation and that increased cAMP levels can reverse the profibrotic myofibroblastic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, scanning and quantifying cGMP dependent PDE isoenzymes was performed on 12 days serum induced myofibroblasts and reveal 5 different transcript expression. Expression of these specific PDEs seems to have a central role in modulating cGMP (Qvigstad et al 2009, Vettel et al 2014, thus modulating the ANP/NPRA system. Lu et al (2013) quantified PDEs in TGF-β induced cardiac myofibroblasts obtained from Sprague-Dawley rats, and their studies have showed that cAMP can prevent the CFs to myofibroblasts transformation and that increased cAMP levels can reverse the profibrotic myofibroblastic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, endothelial dysfunction contributes to cardiac fibrosis via the reduced bioavailability of NO, known to exert direct anti-fibrotic effects involving the cyclic guanosine monophosphate (cGMP) pathway [41, 42]. Vettel et al [42] recently demonstrated that the cGMP/cyclic adenosine monophosphate (cAMP)-hydrolyzing phosphodiesterase (PDE) 2, which is upregulated in human failing hearts [43], leads to a decrease in cAMP levels in cardiac fibroblasts and accelerates the conversion of fibroblasts to myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Vettel et al [42] recently demonstrated that the cGMP/cyclic adenosine monophosphate (cAMP)-hydrolyzing phosphodiesterase (PDE) 2, which is upregulated in human failing hearts [43], leads to a decrease in cAMP levels in cardiac fibroblasts and accelerates the conversion of fibroblasts to myofibroblasts. Exogenous activation of cGMP via atrial natriuretic peptide (ANP) or NO was able to bypass the PDE2-mediated degradation of cAMP and reversed the differentiation of fibroblasts into myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…2 In engineered connective tissue, phosphodiesterase 2 enhances the conversion of fibroblasts to myofibroblasts, thereby increasing tissue stiffness. 3 Finally, phosphodiesterase 2 inhibitors induce relaxation of pulmonary arteries and inhibit proliferation of pulmonary arterial smooth muscle cells, indicating that phosphodiesterase 2 inhibitors may constitute an effective strategy for treatment of pulmonary hypertension. 4 On this background, published in this issue of Hypertension, a study by Li et al 5 adds a new facet to the emerging roles of phosphodiesterase 2 in the pathophysiology of cardiovascular diseases.…”
mentioning
confidence: 99%
“…1 Moreover, in the study of Li et al 5 on sympathetic neurons, phosphodiesterase 2A exhibited the properties of a cGMP-specific phosphodiesterase (Figure), but in other systems phosphodiesterase 2 regulates both cAMP and cGMP. 3,4 This may reflect differential compartmentalization of proteins involved in cAMP and cGMP signaling.…”
mentioning
confidence: 99%